Judah and the Judeans in the Persian Period: [conference, "Judah and the Judeans in the Achaemenid period", that took place in Heidelberg on 15 - 18 July, 2003] - Lipshits, ʿOded; Oeming, Manfred (Eisenbrauns, 2006)
Pt. 1. Historical, epigraphical, and archaeological perspectives -- pt. 2. Biblical perspectives
Literaturangaben
Keywords: Bible -- Old Testament -- Criticism, interpretation, etc -- Congresses; Yehud (Persian province) -- Congresses; Judaea (Region) -- History -- Congresses; Konferenzschrift; Konferenzschrift -- 2003 -- Heidelberg; Geschichte 539 v. Chr.-332 v. Chr.; Iran; Israel; Achämeniden; Heidelberg <2003>; Judäa